2012
DOI: 10.1038/srep00507
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid doses for evacuees from the Fukushima nuclear accident

Abstract: A primary health concern among residents and evacuees in affected areas immediately after a nuclear accident is the internal exposure of the thyroid to radioiodine, particularly I-131, and subsequent thyroid cancer risk. In Japan, the natural disasters of the earthquake and tsunami in March 2011 destroyed an important function of the Fukushima Daiichi Nuclear Power Plant (F1-NPP) and a large amount of radioactive material was released to the environment. Here we report for the first time extensive measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(115 citation statements)
references
References 16 publications
(17 reference statements)
6
108
0
1
Order By: Relevance
“…They found detectable 131 I activity in 39 of the 45 people evacuated from coastal areas, and in 7 of the 17 residents in Tsushima District (Namie Town). Thyroid equivalent doses by inhalation ranged from none detected to 33 mSv (19). The median thyroid equivalent doses for children and adults were 4.2 and 3.5 mSv, respectively.…”
mentioning
confidence: 99%
“…They found detectable 131 I activity in 39 of the 45 people evacuated from coastal areas, and in 7 of the 17 residents in Tsushima District (Namie Town). Thyroid equivalent doses by inhalation ranged from none detected to 33 mSv (19). The median thyroid equivalent doses for children and adults were 4.2 and 3.5 mSv, respectively.…”
mentioning
confidence: 99%
“…The Japanese government carried out a screening survey for 1,062 children living near the nuclear plant and reported that no child had an equivalent thyroid dose of more than 50 mSv. Tokonami et al also measured radioiodine activity in thyroid in situ [ 6 ]. Radioiodine activity determined by a whole-body counter in the volunteer workers at the shelter facilities is presented by Kinashi et al in Chap.…”
Section: Internal Dose Estimationmentioning
confidence: 99%
“…It is estimated that 160, 88, 18, and 15 PBq of 131 I, 132 Te, 134 Cs, and 137 Cs, respectively, were discharged from the Fukushima Daiichi NPP into the environment [43]. A primary health concern for internal exposure to 131 I is the potential development of thyroid cancer, since the thyroid gland is most sensitive to 131 I [44]. Examples of deterministic health effects induced by inhalation of β-emitting 131 I include bone marrow depression (1-10 Gy), hypothyroidism (10-100 Gy), and ablation of the thyroid gland (100-100 Gy).…”
Section: Radionuclides Released From the Fukushima Daiichi Nuclear Pomentioning
confidence: 99%
“…Once 131 I is taken up by the thyroid gland, a constant bombardment of surrounding tissue can overwhelm the repair mechanisms of cells and trigger cancer [3]. Tokonamii et al calculated the median thyroid equivalent dose to 4.2 and 3.5 mSv for children and adults, respectively [44].…”
Section: Radionuclides Released From the Fukushima Daiichi Nuclear Pomentioning
confidence: 99%